Default mode network functional connectivity after multiple concussions in children and adolescents. (24th December 2019) - Plourde, Vickie; Rohr, Christiane S; Virani, Shane; Bray, Signe; Yeates, Keith Owen; Brooks, Brian L
Abstract: : The default mode network (DMN), a set of brain regions, has been shown to be affected post-concussion. Objective: This cross-sectional study aims to elucidate if children and adolescents with multiple concussions demonstrate long-term alterations in DMN functional connectivity (FC). Method: Participants ( N = 57, 27 girls and 30 boys; 8-19 years old, M age = 14.7, SD = 2.8) were divided into three groups (orthopedic injury [OI] n = 20; one concussion n = 16; multiple concussions n = 21, M = 3.2 concussions, SD = 1.7) and seen on average 31.6 months post-injury (range 4.3-130.7 months; SD = 19.4). They underwent a resting-state functional magnetic resonance imaging scan. Parents completed the ADHD rating scale-5 for children and adolescents. Children and parents completed the post-concussion symptom inventory (PCSI). Results: Anterior and posterior DMN components were extracted from the fMRI data for each participant using FSL's MELODIC and dual regression. We tested for pairwise group differences within each DMN component in FSL's Randomize (5000 permutations) using threshold-free cluster enhancement to estimate cluster activation, controlling for age, sex, and symptoms of inattention. FC of the anterior DMN was significantly reduced in the group with multiple concussions compared to the two other groups, whereas there were no significant group differences on FC of the posterior DMN. There were no significant associations between DMN FC and PCSI scores. Conclusions: These results suggest reduced FC in the anterior DMN in youth with multiple concussions, but no linear association with post-concussive symptoms.